A Rare Case of Triple Malignancy: Non Hodgkin Lymphoma, Carcinoma of Breast and Squamous Cell Carcinoma of Tongue in a Single Patient - Haque, Md Ehteshamul; Karim, Shahnaz; Siddiqui, Md Mahmudur Rahman; Kareem, Mayesha; Khatun, Amena (Anwer Khan Modern Medical College Journal, 2018)
We are reporting a case of having triple malignancy including Non Hodgkin Lymphoma (NHL), Carcinoma breast, Squamous cell carcinoma (SCC) of the tongue. Triple malignancy is a very rare occurrence. Cancer patient are at increased risk of developing a subsequent primary tumour. Prevalence of multiple primary malignancies is slowly increasing due to prolonged survival of cancer patients with advances in diagnostic and therapeutic modalities. The reasons may be environmental modifications, genetic predisposition or therapy-induced. People who have had non-Hodgkin lymphoma (NHL) can get any type of second cancer, but they have an increased risk of certain cancers, including carcinoma lung, skin, tongue, bladder, colon, kidney etc. Radiation therapy to the chest increases the risk of breast cancer. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 75-78